Flavour generation during commercial barley and malt roasting operations: A time course study - Yahya H.; Linforth R.S.T.; Cook D.J. (2024)
The roasting of barley and malt products generates colour and flavour, controlled principally by the time course of product temperature and moisture content. Samples were taken throughout the industrial manufacture of three classes of roasted product (roasted barley, crystal malt and black malt) and analysed for moisture content, colour and flavour volatiles. Despite having distinct flavour characteristics, the three products contained many compounds in common. The product concentrations through manufacture of 15 flavour compounds are used to consider the mechanisms (Maillard reaction, caramelisation, pyrolysis) by which they were formed. The use of water sprays resulted in transient increases in formation of certain compounds (e.g., 2-cyclopentene-1,4-dione) and a decrease in others (e.g., pyrrole). The study highlights rapid changes in colour and particularly flavour which occur at the end of roasting and onwards to the cooling floor. This highlights the need for commercial maltsters to ensure consistency of procedures from batch to batch. 2013 Elsevier Ltd. All rights reserved.